STUDY OF VITAMIN D3-FORTIFIED GOAT KEFIR ON PLASMA FIBRINOGEN LEVELS OF DIABETIC RATTUS NORVEGICUS RATS - Tania Masha; Astika Widy Utomo; Martha Ardiaria; Ahmad Syauqy; Ayu Rahadiyanti; Choirun Nissa; Mutiara Irma Maharani; Fairuz Zulfa; Binar Panunggal (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2023)
ABSTRACTBackground: Diabetes mellitus is often associated with the occurrence of complications. Haemostatic factors, especially hyperfibrinogenaemia, is a common cause of the complication. Goat kefir and vitamin D3 may act as an antioxidant and anti-inflammation agent which can repair pancreatic beta cells.Objectives: This study aimed to analyse the effect of vitamin D3-fortified goat milk and plasma fibrinogen levels in diabetic rats. Materials and Methods: This study was an experimental study with pre-post only group design. The samples were 21 male rats divided into four groups; negative control (K-), positive control (K +), treated with unfortified goat kefir (P1), and treated with vitamin D3-fortified goat kefir (P2). The 35-day intervention was conducted, the goat kefir dose was 2 ml/200 g BW/day and the vitamin D dose 600 IU. Fasting blood glucose and plasma fibrinogen were assessed pre- and post-intervention. Blood glucose level was evaluated by GOD-PAP method, while plasma fibrinogen was assessed by Enzyme-Linked Immunosorbent Assay (ELISA) method. The data were analysed with paired t-test and One-Way ANOVA. Results: There were not significant difference levels of fibrinogen between groups. The intervention groups both showed an insignificant decrease of plasma fibrinogen. The plasma fibrinogen of group treated with vitamin D3-fortified goat kefir went down to 13.47 mg/dl from 16.49 mg/dl (p = 0.49). Meanwhile, the group treated with unfortified goat kefir showed a decrease from 26.81 mg/dl to 24.94 mg/dl (p=0.83). On the other hand, there was a significant decrease in fasting blood glucose in the group treated with vitamin D3-fortified goat kefir from 181.75 mg/dl to 116.25 mg/dl (p=0.03).Conclusion Our results demonstrate that administration of vitamin D3-fortified goat kefir can decrease fasting blood glucose but not in plasma fibrinogen. Keywords : Diabetes Mellitus; Fastin blood glucose; Fibrinogen; Goat kefir; Vitamin D3 Fortification